Educational Games of Introducing English to Early Childhood - Gunawan, Rico Ferdian; Chandrawati, T. Brenda; Prasetya, FX. Hendra (Journal of Business and Technology, 2024)
In early childhood, they usually begin exploring many things, such as learning, playing and imitating the behaviour of older people. Children learn to communicate with others and from their peers at a certain age. Children also learn to recognize letters of the alphabet, self-recognition and surrounding objects. The following year, children recognize other languages, such as English. Then, year by year, children start learning many languages, such as English. This educational game will be for English furniture for children. When children play games, they are usually accompanied by parents to guide and teach them to play games. The educational game "Elang" is for learning English using puzzle gameplay. This "Elang" game will introduce fruits, transportation, and family members. Then, children can be through an educational game, when children are playing games, of course, accompanied by their parents to guide and teach them to play the game. The purpose of making this educational game is to use puzzle gameplay that brings the topic of fruit introduction, transportation introduction and family introduction to children. The research methods used are waterfall methods and game testing to collect data from respondents in a survey. The survey was conducted by interviewing parents of children who played the educational game "Elang". The survey results show that the educational game "Elang" introduction to English can be efficient in early childhood learning.